2006
DOI: 10.1021/jo060945k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bulky and Electron-Rich MOP-type Ligands and Their Applications in Palladium-Catalyzed C−N Bond Formation

Abstract: A series of 2-dialkylphosphino-2'-alkoxy-1,1'-binaphthyl ligands (6a-c and 8a-c) have been prepared conveniently by a lithium-initiated ring-opening reaction of dinaphthofuran, followed by selective phosphorylation. These compounds displayed a remarkable air and moisture stability, both in solid form and in solution. Application of these phosphine ligands in palladium-catalyzed C-N bond forming reactions revealed the crucial roles of the steric bulk of the substituents on the phosphorus atom governing the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 40 publications
0
65
0
1
Order By: Relevance
“…[8] There now exist several ligand classes that promote such difficult C À N coupling reactions of aryl chlorides, including ( Figure 1) bulky trialkylphosphanes, [9][10][11][12] N-heterocyclic carbenes, [13][14][15] biaryldialkylphosphanes [7] and chelating bisphosphanes, [16,17] as well as N-or O-heteroatom-functionalized phosphanes. [18][19][20][21][22][23][24][25][26] More recently, difficulties associated with particularly challenging classes of amine substrates have been addressed by the use of specialized task-specific ligands in combination with a judiciously selected Pd precursor. These reactivity challenges include the selective monoarylation of small primary alkylamines (including methylamine), [19,27] the arylation of poorly nucleophilic [27][28][29] or heteroatom-functionalized anilines, [30][31][32] the coupling of base-sensitive substrates, [33] the arylation of lithium amide, [34,35] and the synthesis of anilines from ammonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] There now exist several ligand classes that promote such difficult C À N coupling reactions of aryl chlorides, including ( Figure 1) bulky trialkylphosphanes, [9][10][11][12] N-heterocyclic carbenes, [13][14][15] biaryldialkylphosphanes [7] and chelating bisphosphanes, [16,17] as well as N-or O-heteroatom-functionalized phosphanes. [18][19][20][21][22][23][24][25][26] More recently, difficulties associated with particularly challenging classes of amine substrates have been addressed by the use of specialized task-specific ligands in combination with a judiciously selected Pd precursor. These reactivity challenges include the selective monoarylation of small primary alkylamines (including methylamine), [19,27] the arylation of poorly nucleophilic [27][28][29] or heteroatom-functionalized anilines, [30][31][32] the coupling of base-sensitive substrates, [33] the arylation of lithium amide, [34,35] and the synthesis of anilines from ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] More recently, difficulties associated with particularly challenging classes of amine substrates have been addressed by the use of specialized task-specific ligands in combination with a judiciously selected Pd precursor. These reactivity challenges include the selective monoarylation of small primary alkylamines (including methylamine), [19,27] the arylation of poorly nucleophilic [27][28][29] or heteroatom-functionalized anilines, [30][31][32] the coupling of base-sensitive substrates, [33] the arylation of lithium amide, [34,35] and the synthesis of anilines from ammonia. [35][36][37][38] However, the structural complexity that is introduced in order to address these specific reactivity challenges 2 , these structurally simple and air-stable P,N ligands enable the cross-coupling of aryl and heteroaryl chlorides, including those bearing as substituents enolizable ketones, ethers, esters, carboxylic acids, phenols, alcohols, olefins, amides, and halogens, to a diverse range of amine and related substrates that includes primary alkyl-and arylamines, cyclic and acyclic secondary amines, NÀH imines, hydrazones, lithium amide, and ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…These factors have limited the use of the coupling of amines to produce less expensive intermediates and commodity building blocks. 6,7 (1) Three general classes of reagents react slowly and require high loading of catalyst, even with most of the most recently developed systems: 8 (1) primary alkylamines, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] which form substantial amounts of product from diarylation in the absence of an ortho substituent on the haloarene reagent or an excess of the primary amines; (2) heteroaryl halides, 11,12,15,17,19,[24][25][26][27][28][29][30][31][32] which are important for medicinal chemistry applications, but have reacted more slowly, with narrower scope, and with higher catalyst loadings than aryl halides; and (3) aryl iodides, which react more slowly and provide lower yields than aryl bromides in couplings with amine nucleophiles, 15,17,[33][34][35][36][37][38][39][40][41][42]…”
Section: Introductionmentioning
confidence: 99%
“…BINAP, BINAP-Tol, DPPF, DiPPF, f-binaphane) and ten phosphine oxides listed in our previous publication, 32 did not show acceptable results. Recently, it was reported that bulky and electron-rich MOP-type ligands were used in palladium-catalyzed C-N bond forming reactions, 33 which also showed good catalytic activity in palladium-catalyzed α-arylation of 1,3-dicarbonyl compounds. 34 We chose one of these ligands 2-dicyclohexylphosphino-2'-methoxy-1,1'-binaphthyl that gave an acceptable yield of desired product from a primary amine (2, Entry 2).…”
Section: Resultsmentioning
confidence: 99%